Involvement of estrogen receptor β in terminal differentiation of mammary gland epithelium - Förster, Carola (National Academy of Sciences, 2002)
The mammary glands of prepubertal estrogen receptor (ER)β−/− mice are morphologically indistinguishable from those of WT littermates. It appears that, although ERβ is expressed in the mouse mammary gland, it is not involved in ductal growth of the gland. In this study, we examined the possibility that ERβ has a role in the differentiated function of the mammary gland. Pregnancy is rare in ERβ−/− mice, but an intensive breeding program produced seven pregnant ERβ−/− mice, of which five did not eat their offspring and continued to successful lactation. Histomorphological comparison of lactating glands revealed that alveoli were larger and there was less secretory epithelium in ERβ−/− than in WT mice. Ultrastructural analysis showed abundant milk droplets and normal apical villi in the luminal epithelial cells, but the extracellular matrix and lamina basalis were reduced, and very frequently the interepithelial cell space was increased. Levels of the adhesion molecules, E-cadherin, connexin 32, occludin, and integrin α2 were reduced, and no zona occludens was detectable. In addition, there was widespread expression of the proliferation marker, Ki-67, in luminal epithelial cells in ERβ−/− but not in WT mice. These findings suggest a role for ERβ in organization and adhesion of epithelial cells and hence for differentiated tissue morphology. We speculate that, because a reduced risk for breast cancer is conferred on women who breast-feed at an early age, ERβ could contribute to this risk reduction by facilitating terminal differentiation of the mammary gland.